Advantages and disadvantages of the virtual teaching modality perceived by the students in an introduction to clinical medicine course of a school of medicine in Lima, Peru - Lecarnaqué Rojas , César G. (2024)
The COVID-19 pandemic forced the school of medicines to opt for a virtual teaching modality due to the suspension of face-to-face activities imposed by the lockdown. Objective: To determine the advantages and disadvantages of the virtual teaching modality perceived by the students in an introduction to clinical medicine course of a school of medicine in Lima, Peru. Methods: A virtual non-validated survey was circulated among fourth year medical students. Results: 94 studentes answered the survey (51%). Perceived advantages were to have more time to study (57.4%) and saving time in transportation (39.4%). The disadvantages were lack of contact with real patients (42.6%) and not to be able to obtain a clinical history from patients (39.4%). The 72.3% of students were able to identify the medical problems of patients, but only 24.4% were able to obtain an adequate clinical history and just 9.6% performed an adequate physical examination. Conclusion: The virtual teaching modality allowed the student to have more time for self-study but limited their abilities to obtain a clinical history and to perform a physical examination.